2022
DOI: 10.2147/dddt.s383101
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Challenges of Anti-VEGF Agents and Their Sustained-Release Strategies for Retinal Angiogenesis

Abstract: Currently, the treatment for ocular neovascular diseases, including diabetic macular edema (DME) and age-related macular degeneration (AMD), mainly involves repeated intravitreal injection of anti-vascular endothelial growth factor (VEGF) drugs. Although it can preserve vision, repeated injections are an invasive treatment modality, leading to serious complications and reducing patient adherence to treatment. To reduce the frequency of administration, prolong the time of drug action, and avoid repeated intravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 151 publications
0
13
0
Order By: Relevance
“…[55] The most prevalent therapy for suppressing angiogenesis includes intraocular injection of anti-VEGF (vascular endothelial growth factors) molecules every 4-6 weeks [56] However, numerous challenges have been raised throughout the years with its use. [57] Anti-VEGF therapies were shown to induce a persistent increase in IOPs, [58] contribute to the incidence of retinal tears [59] and geographic atrophy progression, [60] induce corneal endothelial and limbal mesenchymal stem cell injuries due to multiple drug administrations, [61] and reduce the choroid vessel thickness. [62,63] Furthermore, a recent retrospective study showed that anti-VEGF intravitreal administration for wet AMD over a 10-year period still leads to a decline in visual acuity, with persistent retinal fluid in 72% of affected eyes.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…[55] The most prevalent therapy for suppressing angiogenesis includes intraocular injection of anti-VEGF (vascular endothelial growth factors) molecules every 4-6 weeks [56] However, numerous challenges have been raised throughout the years with its use. [57] Anti-VEGF therapies were shown to induce a persistent increase in IOPs, [58] contribute to the incidence of retinal tears [59] and geographic atrophy progression, [60] induce corneal endothelial and limbal mesenchymal stem cell injuries due to multiple drug administrations, [61] and reduce the choroid vessel thickness. [62,63] Furthermore, a recent retrospective study showed that anti-VEGF intravitreal administration for wet AMD over a 10-year period still leads to a decline in visual acuity, with persistent retinal fluid in 72% of affected eyes.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…Age‐related macular degeneration (AMD) is a vision‐threatening condition that involves the abnormal growth of new blood vessels [55] . The most prevalent therapy for suppressing angiogenesis includes intraocular injection of anti‐VEGF (vascular endothelial growth factors) molecules every 4–6 weeks [56] However, numerous challenges have been raised throughout the years with its use [57] . Anti‐VEGF therapies were shown to induce a persistent increase in IOPs, [58] contribute to the incidence of retinal tears [59] and geographic atrophy progression, [60] induce corneal endothelial and limbal mesenchymal stem cell injuries due to multiple drug administrations, [61] and reduce the choroid vessel thickness [62,63] .…”
Section: Ophthalmic Applications Of Hydrogelsmentioning
confidence: 99%
“…Adherence to follow-up for anti-VEGF injections is critical for the effective management of DR and maintaining visual outcomes over the long term. From a pharmacokinetics standpoint, it takes a monthly injection to maintain adequate drug levels if the goal is continuous action of anti-VEGF therapy [ 36 ]. Cessation of monthly injections may promptly result in disease worsening, even in patients who quickly showed improvement and then remained stable over the long term.…”
Section: Efficacy Of Anti-vegf Agents As Primary Treatment For Npdr A...mentioning
confidence: 99%
“…Regular (monthly/bimonthly) administration of anti-VEGF drugs is the approved front-line treatment modality for these patients (17). Delivered through intravitreal injections, frequent administration of anti-VEGF drugs poses a significant clinical burden on healthcare institutions and patients due to the risk of infection, patient anxiety, clinic capacity and availability of trained healthcare personnel among others (18).…”
Section: Introductionmentioning
confidence: 99%